Decolonizing the Environment: Third World Approaches to the Planetary Crisis - Khoday, Kishan (Indonesian Journal of International Law, 2022)
The colonial process transformed the landscape of the Earth with devastating consequence for communities and ecosystems. It also set the foundations of the planetary crisis that we see today. Using a TWAIL approach, this article argues for the relevance of colonial and post-colonial analysis in combatting today’s planetary crisis and advancing a more effective form of global environmental governance. Today’s global order of multilateral agreements is increasingly under criticism, ineffective in combating the planetary crisis and in halting the disproportionate impact of ecological change experienced across the global South. A TWAIL lens helps to understand the root causes of today’s crisis in the colonial past, and to embrace calls by vulnerable communities across the South for equity and justice in environmental decision-making. It brings clarity to the socio-political context from which today’s planetary crisis arose, ways colonial and post-colonial legacies continue to shape today’s multilateral frameworks, and why, despite an array of well-crafted global regimes, the planetary crisis continues to escalate.